Electrochemical SERS and SOERS in a single experiment: A new methodology for quantitative analysis. (20th February 2020) - Hernandez, Sheila; Perales-Rondon, Juan V.; Heras, Aranzazu; Colina, Alvaro
Abstract: In the present work, a new methodology which combines two different phenomena to enhance the Raman signal is used to resolve a mixture of two compounds with similar molecular structures. The use of Raman spectroelectrochemistry (Raman-SEC) allows us to collect simultaneously, with high time-resolution, the enhancement of the Raman signal of the compounds present in a sample during the electrochemical oxidation-reduction cycle (ORC) of a silver screen-printed electrode. During such ORC two different phenomena appears depending on the stage of the electrochemical modification of the silver substrate, which are known as electrochemical surface enhanced Raman scattering (EC-SERS) and electrochemical surface oxidation enhanced Raman scattering (EC-SOERS). This work is a proof of concept that demonstrates the advantage of using EC-SOERS and EC-SERS in a single experiment to resolve mixtures of similar molecules such as vitamin B3, which components are nicotinic acid and nicotinamide. Although the interaction between analytes and substrates influence a univariate calibration, the trilinear character of Raman-SEC makes possible to deconvolve such interactions and provide a good calibration curve for both, nicotinic acid and nicotinamide. Graphical abstract: Image 1